(3Yde GdNQUGJ HGdCYTGH hGdeYGOfs - (3eLghds
(3ChdgG (B:s
(3Yed eQge dGWdGY GdLeQI GdJj JWdY HGdYjf hGdhLg dGfJTGQgG eKd GdYOSI HjVI heOhQI hOGFQgG CShO HGdMGd NQhLNG TdhT Edi bdH GdEfSGfs
(3BNQgG (B:s
(3acGf GdYHO jNQL efg ONGf YXje hcGf jQNj KGfj fbWI cGf jZdj hcGf jQNj KGdK fbWI cGfJ JHQe Ydi hLgg hJZhU HfUg ShGA aGfg jUjQ MLQ dG QhHGUs
(3ecJhH HCcKQ ef NW hQHeG cGfJ ef cJGHjf eNJdajfs
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
Keywords: (3GdcjejGA hGdWHjYjGJs